New Fisheries-related data from the Mediterranean Sea (October, 2015) - Tsagarakis, K.; Basusta, N.; Basusta, A.; Biandolino, F.; Bostanci, D.; Buz, K.; Yedier, S. (Natl Centre Marine Research, 2015)
In this third Collective Article, with fisheries-related data from the Mediterranean Sea, we present the historical length distribution of Lophius budegassa in the catch of commercial trawlers in the Greek seas; length-weight and length-length relationships of five flatfish species (Lepidorhombus boscii, L. whiffiagonis, Platichthys flesus, Pegusa lascaris and Solea solea) from different coastal areas of Turkey (Black Sea and Eastern Mediterranean Sea); growth of settled Polyprion americanus and length-weight relationships of this species and of Deltentosteus quadrimaculatus, Capros aper and three commercially important groupers in the Eastern Mediterranean Sea; the age, growth and mortality of Zosterisessor ophiocephalus in the Eastern Adriatic Sea; the length-weight relationship and condition factor of Atherina boyeri in a Central Mediterranean semi-isolated lagoon, and also the length-weight and length-length relationships of three Alburnus species from different inland waters in Turkey.
Keywords: Weight-length relationships; ichthyology; Aegean Sea; Levantine Sea; fishes; sole; anglerfish; wreckfish